2012
DOI: 10.3140/bull.geosci.1350
|View full text |Cite
|
Sign up to set email alerts
|

Ordovician-Silurian boundary graptolites of the Southern Alps, Austria

Abstract: Seven species of graptoloid graptolites are described from Hirnantian and lower Rhuddanian formations of the Austrian part of the Carnic and western Karavanke Alps. The Plöcken Formation, of latest Ordovician (Hirnantian) age, yields the biozonal index graptolite <i>Metabolograptus persculptus </i>in the Cellon Reference Section and, tentatively, the Feistritzgraben Section. A distinctive graptolite assemblage indicating an earliest Silurian (early Rhuddanian) age comes from the Waterfall Section n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…He suggested that many narrower forms should be reassigned to N. ajjeri, a similar species with narrower width. This idea obtained some support from Štorch & Schönlaub (2012). One of the Chinese N. normalis specimens from the Yangtze region has a relatively wide and blunt proximal end and a small rhabdosome width, which may suggest a close relationship to N. ajjeri (Chen et al 2005, text- fig.…”
mentioning
confidence: 90%
“…He suggested that many narrower forms should be reassigned to N. ajjeri, a similar species with narrower width. This idea obtained some support from Štorch & Schönlaub (2012). One of the Chinese N. normalis specimens from the Yangtze region has a relatively wide and blunt proximal end and a small rhabdosome width, which may suggest a close relationship to N. ajjeri (Chen et al 2005, text- fig.…”
mentioning
confidence: 90%
“…This is the third or fourth Gondwanan record of this uppermost Ordovician assemblage (Underwood et al . ; Loydell ; Štorch & Schönlaub ). Probably the same ‘interregnum’ at high palaeolatitudes may be an equivalent to the uppermost Ordovician Spinachitina oulebsiri–Euconochitina moussegoudaensis chitinozoan assemblage, recorded from northern Chad and SE Libya (Thusu et al .…”
Section: The Bohemo‐iberian Regional Scalementioning
confidence: 99%
“…The overall thickness of Silurian strata does not exceed 60 m. The Silurian transgression in the region started at the beginning of the Llandovery. The duration of the gap separating the Ordovician and Silurian successions is highly variable and a rock succession corresponding to several conodont zones of Llandovery or Llandovery to Early Wenlock age is locally missing (Schönlaub & Histon ; Štorch & Schönlaub ).…”
Section: Geological Settingmentioning
confidence: 99%
“…(), graptolites by Jaeger (), Jaeger et al . (), Štorch & Schönlaub (), foraminifers by Langer (), Kristan‐Tollmann (), ostracods by Schallreuter (), acritarchs by Martin () and subsequently by Priewalder (), chitinozoans by Priewalder (, , ), trilobites by Haas () and Santel () and corals by Pickett (). In addition, after Walliser (), Ferretti & Schönlaub () studied the distribution of conodonts in the Hirnantian in the Cellon section.…”
Section: Geological Settingmentioning
confidence: 99%